Analisis Yuridis Perjanjian Perkawinan Pasca Lahirnya Putusan Mahkamah Konstitusi No 69/PUU-XII/2015 - Putri Ruqiatul Hilal (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
Marriage is a very strong contract (mistaqan ghalidan) to obey Allah's commands and carrying it out is an act of worship. The goal is to realize a household life that is sakinah, mawaddah, and rahmah. In the realization of a household with the bonds of marriage there are components that cover it, both in terms of regulations and legal concepts. Basically, a marriage agreement is a form of protection or protection if in the future there are things that are not desired by both parties such as death, divorce or bankruptcy, the legal basis regarding the marriage agreement itself has been regulated in the Compilation of Islamic Law and the Marriage Law Number 1 of 1974 and the Constitutional Court Decision No. 69 / PUU-XII / 2015, After the birth of the Constitutional Court Decision Number 69 / PUU / XII / 2015, the marriage agreement has changed both in terms of the time of creation and the institution that has the authority to ratify the marriage agreement.